Corruption in Higher Education: Old Problems and New Challenges - Denisova-Schmidt, Elena (International Higher Education, 2025)
<h3 id="corruption-in-higher-education-threatens-academic-integrity-and-public-trust-in-universities-worldwide-issues-like-bribery-plagiarism-and-ai-assisted-cheating-are-exacerbated-by-financial-pressures-and-political-influences-addressing-this-crisis-requires-governance-reforms-ethical-awareness-and-global-collaboration-to-preserve-educations-core-mission-and-prevent-further-erosion-of-academic-standards" data-pm-slice="1 1 []">Corruption in higher education threatens academic integrity and public trust in universities worldwide. Issues like bribery, plagiarism, and AI-assisted cheating are exacerbated by financial pressures and political influences. Addressing this crisis requires governance reforms, ethical awareness, and global collaboration to preserve education’s core mission and prevent further erosion of academic standards.